DECISION-MAKING UNDER QUOTA CONSTRAINTS: DISCRETION AMONG STREET-LEVEL BUREAUCRATS IN SUBSIDIZED HEALTH INSURANCE IMPLEMENTATION AT THE SERANG CITY SOCIAL SERVICE OFFICE - Novita Sari; Bambang Shergi Laksmono (RADJA PUBLIKA, 2026)
This study examines how street-level bureaucrats (SLBs) make decisions under quota constraints in implementing subsidized health insurance, particularly the Contribution Assistance Recipient (PBI) scheme under Indonesia’s national health insurance system (BPJS), at the Social Service Office of Serang City, Indonesia. It addresses the challenges of limited resources and increasing service demand that require SLBs to adapt policy practices in real-world conditions. Using a qualitative descriptive approach, data were collected through in-depth interviews, observations, and document analysis involving key implementers. The findings reveal that discretion plays a central role, operating through practices such as restricting access and demand, administrative differentiation, regulation of client interactions and work situations, and influencing client behavior. Each decision made by SLBs determines access to health services for the poor and directly affects social welfare. These practices function as coping mechanisms that enable SLBs to manage workload pressures and allocate limited quota. However, discretion also has a dual nature: while it enhances flexibility and responsiveness, particularly in prioritizing vulnerable groups, it may also introduce risks to fairness and accountability. The study concludes that discretion operates within a complex interplay of institutional constraints and socio-political pressures, highlighting the need for balanced governance to ensure both adaptability and accountability in policy implementation.